Spectrum Antimicrobial Agent Displayed Potent Growth Inhibitory Effect Toward Non-Small Cell Lung Cancer - Dr Sunil Bhatt (Genius Journals, 2022)
Following the synthesis of a variety of novel 6-aryl-5-cyano thiouracil derivatives, research was conducted to explore the antibacterial, antifungal, and anticancer effects of these compounds. When tested against the Gram-positive bacteria S. aureus and B. subtilis, the findings of the antimicrobial test indicated that compounds 7b and 7c had a greater degree of antibacterial activity than the reference drug amoxicillin. Compound 4i was shown to be an antibacterial agent with a broad spectrum, and it also displayed the highest antifungal activity against C. albicans. In addition to this discovery, compound 4i was found to be an anticancer agent. In point of fact, the antifungal activity of this medication was significantly higher than that of the standard treatment amphotericin B (MIC = 2.34, compared to 3.00 g/mL for amphotericin B). In line with the methodology devised by the National Cancer Institute (NCI) in the United States of America, certain compounds were examined for their in vitro cytotoxicity at a single concentration of 105 M. When evaluated for their potential to kill kidney cancer cell lines UO-31 and/or A498, the great majority of the compounds were found to have only a modest level of cytotoxic activity, as indicated by the findings of the first screening. Despite this, compounds 6d and 6i displayed a significant growth inhibiting influence on the leukaemia MOLT-4 cell line as well as the non-small cell lung cancer HOP-92 cell line.
Keywords: 6-aryl-5-cyano thiouracils; antibacterial; antifungal; anticance